PEMBERIAN EKSTRAK ETANOL BUAH BUNCIS (Phaseolus vulgaris L.) UNTUK MENURUNKAN KOLESTEROL TOTAL, Low Density Lipoprotein (LDL) DAN MENINGKATKAN High Density Lipoprotein (HDL) PADA TIKUS WISTAR DIET TINGGI LEMAK - Wahjuni, Sri; Rustini, Ni Luh; Yuliantari, Putu (Jurnal Kimia (Journal of Chemistry), 2016)
Excessive fat consumption can increase blood cholesterol level. Phytosterol composition in the plant can decrease blood cholesterol level. One of the plants that contain phytosterol is beans. This study was to prove the effect of antihypercholesterol the ethanol extract of the beans ( Phaseolus vulgaris L .) with variety of doses of 50 mg/Kg BW; 100 mg/Kg BW and 150 mg/Kg BW in male Wistar rats with high fat level condition. Subjects of this study were 24 Wistar rats divided into 6 groups randomly with posttest control group study design. First group as negative control, second group as positive control, and the third (high cholesterol diet and ethanol extract in dose of 50 mg/kg,bw), fourth ( high cholesterol diet and ethanol extractin dose of 100 mg/kg,bw), fifth ( high cholesterol diet and ethanol extract in dose of 150 mg/kg,bw),  sixth (high cholesterol diet and simvastatin drug). The data was analyzed with ANOVA Tukey test. The result of this study shows total cholesterol levels decrease 23,88%; 30,14%; 35,82%. Cholesterol LDL levels decrease 38,09%; 52,38%; 61,35%. Cholesterol HDL levels increase 21,86%; 56,56%; 63,84%. Dose variant on this study giving the best result to decrease total cholesterol levels and LDL was 150 mg/Kg BW. Furthermore, 100 mg/Kg BW dose gave the best result to increase HDL cholesterol level. Based on the results it can be suggested that beans ethanol extract is able to decrease total cholesterol level, LDL and increase HDL cholesterol levels.
Keywords: beans, cholesterol, phytosterol, total cholesterol, LDL, HDL